PENGARUH LIKUIDITAS, LEVERAGE, EFISIENSI OPERASI, DIVIDEND PAYPUT RATIO, PROFITABILITAS DAN UKURAN PERUSAHAAN TERHADAP RISIKO SISTEMATIS DAN NON-SISTEMATIS (Studi pada Perusahaan Non-Keuangan Indeks LQ45 Periode 2012-2016) - Januardi, Nana Varian; Arfianto, Erman Denny (Diponegoro Journal of Management, 2017)
Risk is a very important part in investment decision. Therefore, any factors that explain the risk dynamics need further research. There are 2 types of investment risk, systematic risk and non-systematic risk. Liquidity, leverage, operating efficiency, dividend payout ratio, profitability, and company size are financial variables that expected to be a determinants of systematic and non-systematic risks.             The objective of this research is to understand the relationship between liquidity, leverage, operating efficiency, dividend payout ratio, profitability, and company size with systematic and non-systematic risks in Indonesia capital markets. This research was done by observing non-finance companies indexed in LQ45 2016 between 2012 to 2016 (5 years).             The result shows that liquidity has a  negative and significant effect towards systematic and non-systematic risks. Profitability carries negative and significant effect towards systematic risk, operating efficiency and company size carries negative and significant effect towards non-systematic risk.